Implementasi Outdoor Learning untuk Meningkatkan Hasil Belajar Kognitif Mahasiswa pada Mata Kuliah Sistematika Tumbuhan Tinggi - Nugroho, Anwari Adi; Hanik, Nur Rokhimah (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
Outdoor learning was learning that gives students the opportunity to explore the surrounding environment  as a source of learning. Students are required to be able to construct knowledge independently throgh the process of  exploring the learning environment in Systematics of High Plant. This research aims to improve student cognitive learning outcomes through the implementation of outdoor learning in the subject of High Plant Systematics. The method used was classroom action research with 3 cycles. Each cycle consists of four basic stages, namely planning, implementation, observation and reflection. Samples used in this study was 22  fourth semester students of Biology Education Study Program, Faculty of Teaching and Education, University of Veteran Bangun Nusantara Sukoharjo .The study was conducted in March and May 2015. The cognitive learning was measured through the posttest. The results showed that the cognitive learning outcomes of students increased from the first cycle to the second cycle amounted to 27.56% and from the second cycle to the third cycle of 10.20%. Target of cognitive learning outcomes at least achieved grade of 75 in average.